2011
DOI: 10.1161/circresaha.111.255075
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Plakoglobin Is Essential for Differentiation of Cardiac Progenitor Cells to Adipocytes in Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Rationale Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a disease of desmosome proteins characterized by fibroadipogenesis in the myocardium. We have implicated signaling properties of junction protein plakoglobin (PG) in the pathogenesis of ARVC. Objective To delineate the pathogenic role of PG in adipogenesis in ARVC. Methods and Results We generated mice overexpressing PG, either a wildtype (PGWT) or a truncated (PGTR), known to cause ARVC, in the heart; and PG null (PG−/−) embryos. PGWT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
181
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(191 citation statements)
references
References 35 publications
9
181
1
Order By: Relevance
“…It has been reported that alterations in transmembrane proteins and desmosomes may lead to changes in cell signalling, and to adipogenic/fibrogenic proliferation or an imbalance of fatty acid oxidation due to changes in PPAR molecules. 30,31 In our study, we did not find a change in the mRNA expression of any …”
Section: Apoptosis and Adipogenesiscontrasting
confidence: 47%
“…It has been reported that alterations in transmembrane proteins and desmosomes may lead to changes in cell signalling, and to adipogenic/fibrogenic proliferation or an imbalance of fatty acid oxidation due to changes in PPAR molecules. 30,31 In our study, we did not find a change in the mRNA expression of any …”
Section: Apoptosis and Adipogenesiscontrasting
confidence: 47%
“…17 Cardiac adipocytes have been attributed to differentiation of cardiac precursor cells in patients who have arrhythmogenic right ventricular cardiomyopathy. 6 On the other hand, large intracardiac lipomas-particularly those in the right atrium-have never been completely explained. Primary rhabdomyosarcomas of the heart have never been well documented, which suggests that differentiation of cardiac stem cells might not, by itself, account for all primary tumors of the heart, or for these cells' effective participation in myocardial regeneration after injury.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Cardiac lipomas are isolated cases among larger series of cardiac neoplasms. 4 Chen and colleagues 5 and Lombardi and associates 6 proposed that primary tumors of the heart arise from gene mutations and the proliferation of various cell types in the myocardium; however, no unifying hypothesis regarding the development of intra-atrial giant lipomas has been proved. Modern imaging techniques, including improvements in echocardiography, have simplified diagnosis 7 ; the addition of spiral computed tomography (CT) and magnetic resonance imaging (MRI) adds clarity to the extent of these tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to LOF mouse models, gain-of-function (GOF) transgenic mice and zebrafish overexpressing the truncated plakoglobin have been generated (6,7). In GOF models, many characteristic signs of Naxos cardiomyopathy are also observed, including fibrofatty replacement of cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%